(3TQM HGFjI Pi GdQeIs - (3eLghds
(3ChdgG (B:s
(3bGd Ph GdQeg hGSeg fLjdGf Hf YbHg hcfjJg CHh GdMGQK hGfeG bjd dg Ph GdQeg HbhdI(B: (3gd JYQa GdCWdGd HGdhMjO eHGd Yjfjc aeG efgG GdeGA jfScH (Bxxx (3cRGfc ef cdi eaQjI SQH s
(3BNQgG (B:s
(3cGf GYfGb gPg GdaQGN ai JLQOgG hJYQjgG ef GdQjT cQGK bO RGdJ Yfg bThQg hceGFeI, GhgjT bO SbW s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3cJHgG fGSNgG JPcQI deNOheg SjO GdCTQGa HgGA GdedI hGdOjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs